Economia solidária e dinâmica familiar de catadores de materiais recicláveis: um estudo no campo ciência, tecnologia e sociedade - Secco, Letícia Dal Picolo Dal (Universidade Federal de São Carlos, 2014)
Solidary economy in Brazil appeared in the 1980s, when inflation rates and unemployment were high. It encouraged the organization of workers in cooperatives to recover the companies they worked for and that had failed, and thus keep theirjobs. The recyclable waste pickers emerged in Brazil because of the social exclusion that part of the population was exposed, around the 1950s, and began to organize themselves into cooperatives by the need of continue working after the banning of picking at landfills and dumpsites. This organization came in partnership with government, religious institutions, NGOs and universities, among other supporters. Actually, it s observed that cooperatives of recyclable waste pickers are not only composed of ex-pickers of the landfills and dumpsites, but also of other workers that are facing unemployment in current times. For the organization of economic-solidary cooperatives, it is necessary for the pickers to acquire knowledge about the nature of the project and about the progress of work. They also need the promotion of the socio-technical adaptations (STA) for the development of social technologies (TS) that that allow their development and sustainability. This process, which influences the organizational form of the enterprise, depending on how it occurs, it will need the partnership between the various agents involved in the movement of solidary economy. The consideration of various knowledges in search of a suitable scientific and technological production that benefits the people, is in keeping of the principles of the field science, technology and society (STS). Whereas that the economic and social inclusion and the labor have influence in the life of the individual and that the solidary economy with their values - solidary, individual freedom, income distribution equally, associative or cooperative organization of work and self-management-, proposes a new form of organization the work, as well as providing the economic and social inclusion, the objective of this work it to investigate the influences of labor economic-solidary relations in the family dynamics of the recyclable waste pickers. The method used is the oral history, and semi-structured interviews were conducted to collect stories about the lives of family groups of the pickers, who are members of a joint economic-solidary cooperative (COOPERVIDA) located in the city of São Carlos-SP. The interviews were transcribed and after they were validated by the interviewed people, by the transcriation process. After this validation, the transcribed data were analyzed using the technique of content analysis. Before the interviews, it was done a field work in the cooperative, with the use of the participant observation technique which was conducted in search of understanding how internal working relationships occur and how the solidary economy and cooperative working relationships traverses the environment. Among the results, we can cite the lack of AST that contribute to the organization of work processes in the cooperative; the economic and solidary principles permeate the relationships in the cooperative, but not entirely; that there is a demand for training of new cooperative to acquire knowledge about the work; families presented influences of the relations of economic-solidary work in their family dynamics, organizing their routine in a egalitarian and solidary way; and that even without being able to define what is solidary economy, the collectors and families develop behavior permeated by its principles. It s indicated the need to develop state policy, including family in programs and actions performed.
Keywords: Economia solidária; Cooperativas de catadores; Materiais - reciclagem; Ciência, tecnologia e sociedade; Dinâmica familiar; Solidary economy; Recyclable waste pickers cooperative; Science, technology and society; Family dynamics; OUTROS